2022 30th International Symposium on Modeling, Analysis, and Simulation of Computer and Telecommunication Systems (MASCOTS) 2022
DOI: 10.1109/mascots56607.2022.00017
|View full text |Cite
|
Sign up to set email alerts
|

Energy Optimal Activation of Processors for the Execution of a Single Task with Unknown Size

Abstract: A key objective in the management of modern computer systems consists in minimizing the electrical energy consumed by processing resources while satisfying certain target performance criteria. In this paper, we consider the execution of a single task with unknown size on top of a service system that offers a limited number of processing speeds, say N , and investigate the problem of finding a speed profile that minimizes the resulting energy consumption subject to a deadline constraint. Existing works mainly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The analysis in [11] of the performance achieved on real clusters demonstrated that the difference between the total costs (based on jobs performance) obtained by our models and the measured costs on the real system is below 13% (significantly lower than the savings, in 32-80% range, we achieved with respect to other methods as it will be demonstrated in Section VII). Finally, the paper in [17], which serves as the foundation for the development of our stochastic scheduler, is included in Section V for comprehensive coverage. This paper presents an analytical model for the ideal scheduling of individual Deep Learning jobs within a system based on GPUs.…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…The analysis in [11] of the performance achieved on real clusters demonstrated that the difference between the total costs (based on jobs performance) obtained by our models and the measured costs on the real system is below 13% (significantly lower than the savings, in 32-80% range, we achieved with respect to other methods as it will be demonstrated in Section VII). Finally, the paper in [17], which serves as the foundation for the development of our stochastic scheduler, is included in Section V for comprehensive coverage. This paper presents an analytical model for the ideal scheduling of individual Deep Learning jobs within a system based on GPUs.…”
Section: Related Workmentioning
confidence: 99%
“…The model presented in this section was first introduced in a previous work [17]. In Section VI, we will rely on this model to solve the global optimization problem heuristically by using the optimal GPU allocation for each job in isolation and then by constructing a global schedule by superposing each individual schedule.…”
Section: A Problem Formulationmentioning
confidence: 99%
See 3 more Smart Citations